Predictive models for the shelf-life of Australian vacuum-packed beef and lamb: Development and evaluation - Chawalit Kocharunchitt; Ian Jenson; Mandeep Kaur; John Sumner; Long Huynh; John P. Bowman; Tom Ross (Food Microbiology, 2026)

Multimodal creativity assessments following acute and sustained microdosing of lysergic acid diethylamide - Robin J. Murphy; Rachael L. Sumner; Kate Godfrey; Acima Mabidikama; Reece P. Roberts; Frederick Sundram; Suresh Muthukumaraswamy (Psychopharmacology, 2025)
Introduction Enhanced creativity is often cited as an effect of microdosing (taking repeated low doses of a psychedelic drug). There have been recent efforts to validate the reported effects of microdosing, however creativity remains a difficult construct to quantify. Objectives The current study aimed to assess microdosing’s effects on creativity using a multimodal battery of tests as part of a randomised controlled trial of microdosing lysergic acid diethylamide (LSD). Methods Eighty healthy adult males were given 10 µg doses of LSD or placebo every third day for six weeks (14 total doses). Creativity tasks were administered at a drug-free baseline session, at a first dosing session during the acute phase of the drug’s effects, and in a drug-free final session following the six-week microdosing regimen. Creativity tasks were the Alternate Uses Test (AUT), Remote Associates Task (RAT), Consensual Assessment Technique (CAT), and an Everyday Problem-Solving Questionnaire (EPSQ). Results No effect of drug by time was found on the AUT, RAT, CAT, or EPSQ. Baseline vocabulary skill had a significant effect on AUT and RAT scores. Conclusions Despite participants reporting feeling more creative on dose days, objective measurement found no acute or durable effects of the microdosing protocol on creativity. Possible explanations of these null findings are that laboratory testing conditions may negatively affect ability to detect naturalistic differences in creative performance, the tests available do not capture the facets of creativity that are anecdotally affected by microdosing, or that reported enhancements of creativity are placebo effects.

Advancing Understanding of Chemical Exposures and Maternal-child Health Through the U.S. Environmental Influences on Child Health Outcomes (ECHO) Program: A Scoping Review - Emily S. Barrett; Jennifer L. Ames; Stephanie M. Eick; Alicia K. Peterson; Zorimar Rivera-Núñez; Anne P. Starling; Jessie P. Buckley; Barbara O‟Brien; Lisa Peterson; Patrick Parsons; Kannan Kurunthacalam; Manish Arora; et al. (Current Environmental Health Reports, 2024)
Purpose of Review Environmental chemical exposures may disrupt child development, with long-lasting health impacts. To date, U.S. studies of early environmental exposures have been limited in size and diversity, hindering power and generalizability. With harmonized data from over 60,000 participants representing 69 pregnancy cohorts, the National Institutes of Health’s Environmental influences on Child Health Outcomes (ECHO) Program is the largest study of U.S. children’s health. Here, we: (1) review ECHO-wide studies of chemical exposures and maternal-child health; and (2) outline opportunities for future research using ECHO data. Recent Findings As of early 2024, in addition to over 200 single-cohort (or award) papers on chemical exposures supported by ECHO, ten collaborative multi-cohort papers have been made possible by ECHO data harmonization and new data collection. Multi-cohort papers have examined prenatal exposure to per- and polyfluoroalkyl substances (PFAS), phthalates, phenols and parabens, organophosphate esters (OPEs), metals, melamine and aromatic amines, and emerging contaminants. They have primarily focused on describing patterns of maternal exposure or examining associations with maternal and infant outcomes; fewer studies have examined later child outcomes (e.g., autism) although follow up of enrolled ECHO children continues. The NICHD’s Data and Specimen Hub (DASH) database houses extensive ECHO data including over 470,000 chemical assay results and complementary data on priority outcome areas (pre, peri-, and postnatal, airway, obesity, neurodevelopment, and positive health), making it a rich resource for future analyses. Summary ECHO’s extensive data repository, including biomarkers of chemical exposures, can be used to advance our understanding of environmental influences on children’s health. Although few published studies have capitalized on these unique harmonized data to date, many analyses are underway with data now widely available.

Ontogenetic variation in isotopic niche positions of aquatic consumers in boreal lakes - T. A. Johnston; P. A. Cott; H. K. Swanson; A. D. Ehrman; G. L. Lescord; A. W. Sumner; P.-L. Savage; K. A. Patterson; R. W.-K. Tang; M. J. Heerschap; J. J. Montgomery; J. M. Gunn (Aquatic Sciences, 2024)

A comparison of state-level carbon reduction strategies: A case study of Hawai‘i - Makena Coffman; Paul Bernstein; Maja P. Schjervheim; Sumner La Croix; Sherilyn Hayashida (Energy and Climate Change, 2023)

Opportunities and limitations of large open biodiversity occurrence databases in the context of a Marine Ecosystem Assessment of the Southern Ocean - Anne-Sophie Bonnet-Lebrun; Maxime Sweetlove; Huw J. Griffiths; Michael Sumner; Pieter Provoost; Ben Raymond; Yan Ropert-Coudert; Anton P. Van de Putte (Frontiers in Marine Science, 2023)
The Southern Ocean is a productive and biodiverse region, but it is also threatened by anthropogenic pressures. Protecting the Southern Ocean should start with well-informed Marine Ecosystem Assessments of the Southern Ocean (MEASO) being performed, a process that will require biodiversity data. In this context, open geospatial biodiversity databases such as OBIS and GBIF provide good avenues, through aggregated geo-referenced taxon locations. However, like most aggregated databases, these might suffer from sampling biases, which may hinder their usability for a MEASO. Here, we assess the quality and distribution of OBIS and GBIF data in the context of a MEASO. We found strong spatial, temporal and taxonomic biases in these data, with several biases likely emerging from the remoteness and inaccessibility of the Southern Ocean (e.g., lack of data in the dark and ice-covered winter, most data describing charismatic or well-known taxa, and most data along ship routes between research stations and neighboring continents). Our identification of sampling biases helps us provide practical recommendations for future data collection, mobilization, and analyses.

Development of an Analytical Method for Assessment of Silver Nanoparticle Content in Biological Matrices by Inductively Coupled Plasma Mass Spectrometry - Eric P. Poitras; Michael A. Levine; James M. Harrington; Amal S. Essader; Timothy R. Fennell; Rodney W. Snyder; Sherry L. Black; Susan S. Sumner; Keith E. Levine (Biological Trace Element Research, 2015)

Climate change and Southern Ocean ecosystems I: how changes in physical habitats directly affect marine biota - Andrew J. Constable; Jessica Melbourne‐Thomas; Stuart P. Corney; Kevin R. Arrigo; Christophe Barbraud; David K. A. Barnes; Nathaniel L. Bindoff; Philip W. Boyd; Angelika Brandt; Daniel P. Costa; Andrew T. Davidson; Hugh W. Ducklow; et al. (Global Change Biology, 2014)
Antarctic and Southern Ocean ( ASO ) marine ecosystems have been changing for at least the last 30 years, including in response to increasing ocean temperatures and changes in the extent and seasonality of sea ice; the magnitude and direction of these changes differ between regions around Antarctica that could see populations of the same species changing differently in different regions. This article reviews current and expected changes in ASO physical habitats in response to climate change. It then reviews how these changes may impact the autecology of marine biota of this polar region: microbes, zooplankton, salps, Antarctic krill, fish, cephalopods, marine mammals, seabirds, and benthos. The general prognosis for ASO marine habitats is for an overall warming and freshening, strengthening of westerly winds, with a potential pole‐ward movement of those winds and the frontal systems, and an increase in ocean eddy activity. Many habitat parameters will have regionally specific changes, particularly relating to sea ice characteristics and seasonal dynamics. Lower trophic levels are expected to move south as the ocean conditions in which they are currently found move pole‐ward. For Antarctic krill and finfish, the latitudinal breadth of their range will depend on their tolerance of warming oceans and changes to productivity. Ocean acidification is a concern not only for calcifying organisms but also for crustaceans such as Antarctic krill; it is also likely to be the most important change in benthic habitats over the coming century. For marine mammals and birds, the expected changes primarily relate to their flexibility in moving to alternative locations for food and the energetic cost of longer or more complex foraging trips for those that are bound to breeding colonies. Few species are sufficiently well studied to make comprehensive species‐specific vulnerability assessments possible. Priorities for future work are discussed.

Decline in voluntary activation contributes to reduced maximal performance of fatigued human lower limb muscles - K. N. Mileva; D. P. Sumners; J. L. Bowtell (European Journal of Applied Physiology, 2012)

Human-induced versus historical habitat shifts: identifying the processes that shaped the genetic structure of the threatened grassland legless lizard, Delma impar - Susana P. Maldonado; Jane Melville; Garry N. L. Peterson; Joanna Sumner (Conservation Genetics, 2012)

Case study on potential agricultural responses to climate change in a California landscape - L. E. Jackson; S. M. Wheeler; A. D. Hollander; A. T. O’Geen; B. S. Orlove; J. Six; D. A. Sumner; F. Santos-Martin; J. B. Kramer; W. R. Horwath; R. E. Howitt; T. P. Tomich (Climatic Change, 2011)

Erratum to: Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2011)

Overlapping functional anatomy for working memory and visual search - Elaine J. Anderson; S. K. Mannan; G. Rees; P. Sumner; C. Kennard (Experimental Brain Research, 2010)

Methods to evaluate normal rainfall for short-term wetland hydrology assessment - Jaclyn P. Sumner; Michael J. Vepraskas; Randall K. Kolka (Wetlands, 2009)

Respiratory modulation in response to high-frequency airway occlusion delivered during inspiration or expiration - David Paul Sumners; Steven P. Hunter; David A. Green (European Journal of Applied Physiology, 2009)

Mask stimulus triggers inhibition in subliminal visuomotor priming - F. Boy; K. Clarke; P. Sumner (Experimental Brain Research, 2008)

Involvement of prefrontal cortex in visual search - E. J. Anderson; S. K. Mannan; M. Husain; G. Rees; P. Sumner; D. J. Mort; D. McRobbie; C. Kennard (Experimental Brain Research, 2007)

Functional analysis of members of the isoflavone and isoflavanone O-methyltransferase enzyme families from the model legume Medicago truncatula - Bettina E. Deavours; Chang-Jun Liu; Marina A. Naoumkina; Yuhong Tang; Mohamed A. Farag; Lloyd W. Sumner; Joseph P. Noel; Richard A. Dixon (Plant Molecular Biology, 2006)

The benefits of multiple mating to female seaweed flies, Coelopa frigida (Diptera: Coelpidae) - D. W. Dunn; J. P. Sumner; D. Goulson (Behavioral Ecology and Sociobiology, 2005)

Contaminant Mobility in Soils Amended with Fly Ash and Flue-Gas Gypsum: Intact Soil Cores and Repacked Columns - C. F. Ishak; J. C. Seaman; W. P. Miller; M. Sumner (Water, Air, & Soil Pollution, 2002)

Is the Arctic Surface Layer a Source and Sink of NOx in Winter/Spring? - B. Ridley; J. Walega; D. Montzka; F. Grahek; E. Atlas; F. Flocke; V. Stroud; J. Deary; A. Gallant; H. Boudries; J. Bottenheim; K. Anlauf; et al. (Journal of Atmospheric Chemistry, 2000)

Arsenate Displacement from Fly Ash in Amended Soils - Nikolla P. Qafoku; Urszula Kukier; Malcolm E. Sumner; William P. Miller; David E. Radcliffe (Water, Air, & Soil Pollution, 1999)